FONDNESS OF PASSENGERS TOWARDS SOUTHERN RAILWAYS WITH REFERENCE TO TIRUCHENDUR RAILWAY STATION (International Journal of Food and Nutritional Sciences, 2022)
We live in a fast-growing world, where the means of travelling is also developing in a speedy way. In all parts of the world, travel operators are competing with each other for giving better facilities to their passengers. Indian Railway is one of the largest rail networks in the world. It was the world’s second largest transport organization under one management. It provides the most convenient and economical mode of transportation to millions of people in the country. Goods transport is the area where railways reap huge amount of income. Operations of Indian Railways have direct impact on passengers as it directly affects the income generation. Madurai division is a passenger-oriented division and earns greater revenue through passenger transit. In order to provide customized services, it is essential to understand the expectations and perceptions of the passengers with regard to quality of services offered by the rail system. Thus, this study takes into account the satisfaction of daily passengers towards the various services offered by the Indian Railway. The primary source includes data collected through structured questionnaire from 120 passengers in Tiruchendur of Madurai division of Southern Railway.